Application of Phytoscreening to Three Hazardous Waste Sites in Arizona - Duncan, Candice M. (Sci Total Environ, 2017)
The great majority of prior phytoscreening applications have been conducted in humid and temperate environments wherein groundwater is relatively shallow (∼1-6 m deep). The objective of this research is to evaluate its use in semi-arid environments for sites with deeper groundwater (>10 m). To that end, phytoscreening is applied to three chlorinated-solvent hazardous-waste sites in Arizona. Contaminant concentrations were quantifiable in tree-tissue samples collected from two of the sites (Nogales, Park-Euclid). Contaminant concentrations were detectable, but not quantifiable, for the third site. Tree-tissue concentrations of tetrachloroethene (PCE) ranged from approximately 400 – 5000 ug/kg wet weight for cottonwood, palo verde, and velvet mesquite at the Nogales site. In addition to standard trunk-core samples, leaf samples were collected to test the effectiveness of a less invasive sampling method. Leaf-sample concentrations were quantifiable, but several times lower than the corresponding core-sample concentrations. Comparison of results obtained for the test sites to those reported in the literature suggest that tree species is a major factor mediating observed results. One constraint faced for the Arizona sites was the relative scarcity of mature trees available for sampling, particularly in areas adjacent to industrial zones. The results of this study illustrate that phytoscreening can be used effectively to characterize the presence of groundwater contamination for semi-arid sites with deeper groundwater.